PENGEMBANGAN MODUL INQUIRY TERBIMBING BERMUATAN NILAI/KARAKTER UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN SIKAP PESERTA DIDIK PADA MATERI JAMUR KELAS XI - Indah Wigati (Bioilmi: Jurnal Pendidikan, 2018)
This study aims to produce a product that is a guided Inquiry module that contains values / characters. This research is a development research developed by Borg & Gall. Data analysis techniques using N-gain score, independent t test and MANOVA test. Product development validation is carried out by material experts, educational media value / character experts. The subjects of this study were students of class X MA Al-Fattah Palembang. Research instruments include modules that are integrated in values / characters, in which there are critical thinking questions and values / characters. Measurement of aspects of critical thinking according to Fascione and attitude based on an integrated questionnaire values / characters according to Einstein consisting of five values / characters namely religious, educational, socio-political, intellectual and practical values. The results of the product research are in the form of modules according to experts "good and" very good ". Learning by using a module shows an increase in the level of critical thinking (average gain score is 0.41), attitude with the value / character: moderate religious value (average score score 0.45), moderate education value (average score score 0.30), moderate socio-political value (average score score 0.32), moderate intellectual value (average score score 0.36) and moderate practical value (average score score 0.35). The Manova test shows that the Sig value is) .00.